2019
DOI: 10.2147/jpr.s177502
|View full text |Cite
|
Sign up to set email alerts
|

<p>Altered amplitude of low-frequency fluctuation and regional cerebral blood flow in females with primary dysmenorrhea: a resting-state fMRI and arterial spin labeling study</p>

Abstract: Purpose: The current study aimed to explore the central mechanism of primary dysmenorrhea (PD) by investigating the alterations in resting state amplitude of low-frequency fluctuation (ALFF) and regional cerebral blood flow (CBF) between PD patients and healthy controls (HCs). Patients and methods: A total of 34 female subjects including 20 PD patients and 14 HCs underwent resting-state functional magnetic resonance imaging (rs-fMRI) and arterial spin labeling technique (ASL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(43 reference statements)
2
18
0
Order By: Relevance
“…Previously, individuals with chronic low back-related leg pain(22) and low back pain(23) showed changed local connectivity and GM volume in the posterior cerebellum. Furthermore, the altered spontaneous activity(31) and glycometabolism(61) in the right posterior cerebellum lobe were detected in the PDM patients that further supported the results of abnormal posterior cerebellar connectivity in our study. Taken together, abnormal connectivity between the pACC and posterior cerebellum may reveal dysfunction in the ACC-cerebellar cognitive and emotion processing circuit in PDM.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Previously, individuals with chronic low back-related leg pain(22) and low back pain(23) showed changed local connectivity and GM volume in the posterior cerebellum. Furthermore, the altered spontaneous activity(31) and glycometabolism(61) in the right posterior cerebellum lobe were detected in the PDM patients that further supported the results of abnormal posterior cerebellar connectivity in our study. Taken together, abnormal connectivity between the pACC and posterior cerebellum may reveal dysfunction in the ACC-cerebellar cognitive and emotion processing circuit in PDM.…”
supporting
confidence: 88%
“…A recent study of the rat model of recurrent headache (30) further demonstrated increased connectivity between the cerebellum and ACC, suggesting the participation of the cerebellum-ACC connectivity in the painrelated process. In PDM women, decreasing spontaneous activity in the right cerebellum posterior lobe (31) and increasing GM volume in the cerebellar tonsil (right VIIIa) (8) have been found. However, whether the cerebellum-ACC connection is aberrant and different cerebellum-ACC circuits correspond to different pain-related processes in PDM remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The precentral gyrus contributes to the provision of pain relief ( Lefaucheur et al, 2001 ). An arterial spin labeling study reported aberrant precentral gyrus activity in patients with PDM ( Zhang et al, 2019 ). Thus, a reduction in the rACC–left precentral gyrus resting-state FC may be the mechanism by which acupuncture affects pain modulation.…”
Section: Discussionmentioning
confidence: 99%
“…A study on classical trigeminal neuralgia by Chen et al [41] showed that the ALFF value of the right precentral gyrus was significantly higher in CTN patients when compared to HCs. Zhang et al [21] found that elevated CBF value was observed in the right precentral gyrus of females with primary dysmenor rhea.…”
Section: Frontal Regionsmentioning
confidence: 97%
“…Hence, ALFF does not completely explain the pathophysiological mechanism of pain. Recent studies have explored the relationship between CBF and rs-fMRI metrics [20,21]. Arterial spinlabelled (ASL) perfusion MRI permits noninvasive quantification of CBF, which can be grouped into three types: continuous labelling, pulsed labelling, and velocity selective labelling [22].…”
Section: Introductionmentioning
confidence: 99%